HUBUNGAN PENGETAHUAN IBU DENGAN CAKUPAN KUNJUNGAN ANTENATAL CARE DI RUMAH SAKIT BHAYANGKARA MAKASSAR - Aisyah aisyah (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
ABSTRACT Objective: The objective of the study was to find out the relationship of maternal knowledge with coverage of Antenatal Care visit at Bhayangkara Makassar Hospital. Method: This research use Cross Sectional Study approach, with sample 30 people, primary data by using questioner, data processing with computerization program and data analysis with Chi-Square. Discussion: Antenatal Care is the care given to pregnant women since the conception until early delivery with Antenatal Care pattern that has not changed for more than 50 years. This care follows the traditional pattern of checking once a month until 28 weeks 'gestation, fortnightly until 36 weeks' gestation and once a week until the baby is born. Result: The result of research have relationship of mother knowledge with coverage of visit of Antenatal Care at Bhayangkara Hospital of Makassar. Conclusion: The knowledge of pregnant women about antenatal care at Bhayangkara Hospital Makassar is mostly with sufficient category knowledge and coverage of antenatal care visits at Bhayangkara Hospital Makassar, mostly in the regular category. Suggestion: The need for motivation from others so that good intentions can manifest into good behavior so it is necessary to form an Antenatal class in order to exchange information to support health efforts